Antidiabetic and immunological effects of ginger rhizome on streptozotocin-nicotinamide induced diabetic rats - Qomi, Mansooreh Sadat Mojani (2013)
The present study was done to determine anti-diabetic and immunological effects of ginger rhizome (Zingiberis officinale) in healthy and nicotinamidestreptozotocin (NA-STZ) induced-diabetic rats. The Characteristics of ginger rhizome were investigated by determination of macronutrients composition using proximate analysis, determination of active components using HPLC method, determination of flavonoid content using aluminium chloride calorimetric assay, total phenolic compound using Folin-Ciocaltea reagent and anti-oxidant activity using DPPH radical scavenging assay. The results showed that young Malaysian ginger which was used for the treatment of rats had high amount of moisture content, less carbohydrate and energy contents compared with the ginger from other regions in previous studies. It had the highest level of 6-gingerol. Total flavonoid and phenolic content was 3.66±0.45 mg quercetin and 10.22±0.87 mg gallic acid per gram of dry weight of rhizome, and DPPH radical scavenging activity was 51.4±0.4% of free radical inhibition. The study was undertaken to determine the effects of ginger rhizome on NASTZ induced-diabetic and healthy rats. Male Sprague-dawley rats were injected a single intraperitoneal dose of nicotinamide prior to STZ. Following 72 hours of injection, those rats with blood glucose level more than 200 mg/dl (equivalent to 11.1 mmol/l) were selected as diabetic rats. A total of 72 rats were divided into 9 groups (4 normal groups and 5 diabetic-induced groups); three different dosages of ginger rhizome were examined (250, 500 and 750 mg/kg body weight). Finally, the results were compared with the control groups. In animal experiments, independent samples t-test showed statistically significant changes in terms of fasting blood glucose, body weight,triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL-c) and tumor necrosis factor- (TNF-) between diabetic and healthy rats following betic induction (p<0.05). Low density lipoprotein (LDL-c), interleukin-6 (IL-6), and C-reactive protein (CRP) remained unchanged. Following 6-weeks intervention, lymphocyte proliferation was impaired in response to the lowest concentration of mitogen (1 g/ml), and T cells in both unstimulated (p=0.001) and stimulated states (p=0.031 for LPS and p=0.001 for PHA) significantly failed to response. Once the levels of stimuli increased to 5 g/ml, the cells showed more activations, but still the decline was noted in diabetic rats (p>0.05). Data from phenotyping assay also demonstrated that the only difference was seen in the percentage of CD4+CD25+ cell numbers (a marker of regulatory T cells) that was higher in diabetic rats (p<0.05). The effects of ginger rhizome on treated group were later analyzed using one-way ANOVA followed by LSD post hoc test. The results indicated that intervention had some inhibitory effects on weight gain; most ginger-treated groups had lower body weight compared with their controls (p<0.01). This finding was well supported by the rats’ food intake. Both blood fasting and plasma glucose of rats were lower in dosages of 250 and 500 mg/kg of diabetic groups compared with the control rats (p<0.05). Total cholesterol and triglyceride did not change following treatment except diabetic rats treated with 250 mg/kg in which the level of triglyceride decreased significantly (p<0.05), LDL-c and HDL-c were significantly decreased in the diabetic group of 500 mg/kg B.W. Decreasing HDL-c led to an increase of the atherogenic indexes in a dose-dependent manner. Supplementation of ginger rhizome showed no effects on the level of CRP in diabetic rats. Levels of IL-6 did not change; nevertheless, levels of TNF- significantly decreased in all the diabetic-treated rats. The efficiency of treatment was evident by changes in p value consistent with increasing dosage of ginger rhizome. In proliferation assay, PHA stimulation with 1 g/ml caused a significant activation in normal group with 250 mg/kg body weight and diabetic groups with two lower ginger concentrations (250 and 500 mg/kg B.W. ). Moreover, PHA stimulation with 5 g/ml produced a considerable proliferation in all the treated groups including glibenclamide (p<0.05); in contrast, stimulation with LPS did not affect any treated groups in two experiments. The results of phenotyping assay reported no significant changes in number of T helper cells (CD3+CD4+), CD4+ alone, percentage of T cells and Natural killer cells,but markers of regulatory T cells (CD4+CD25+) were significantly raised in normal and diabetic rats with dosages of 750 and 500 respectively (p<0.05). The percentage of B cells also significantly increased in the lowest dosage of ginger in both normal and diabetic rats. To sum up, the results clearly showed that ginger rhizome supplementation in lower dosages regulated blood glucose in diabetic condition; also it showed benefits on lowering levels of TG, LDL-c, TNF- and some markers of immune functions. Although the advantages of ginger are evident from the findings of this study and previous literature, further research is recommended to be done in human subjects to confirm the current results.